The roles of nurses in supporting health literacy: a scoping review - Wilandika, Angga; Pandin, Moses Glorino Rumambo; Yusuf, Ah (Frontiers in Public Health, 2023)
Introduction The importance of health literacy in achieving optimum health is highly significant, particularly in the nursing profession where it is an integral part of the roles and functions of nurses. Therefore, this scoping review aims to describe the roles of nurses in promoting patient health literacy and identify the determinant factors of health literacy in nursing practices. Methods An integrative search was conducted through four databases, namely, ScienceDirect, ProQuest, SAGE Journal, and PubMed, using various keyword combinations such as “health literacy,” “health information,” “patient health literacy,” “patient literacy,” and “nurses.” Furthermore, the inclusion criteria employed were peer-reviewed articles focused on the nursing profession, explicitly discussing health literacy related to nursing, and including original studies, such as cross-sectional, quasi-experimental, and qualitative studies. The selected review articles were all published between 2017 and 2022. Results In total, 13 articles met the criteria and were applied in this scoping review. Most of these discuss health literacy related to nursing practice in clinical and community settings, as well as educational institutions. Health literacy is an essential aspect of professional nursing practice. Consequently, the supportive roles of nurses include acting as caregivers, facilitators, and educators to help patients overcome their literacy limitations and attain improved wellbeing. Conclusion Nurses can improve the health literacy skills of patients by making health information related to their illnesses easier to access, understand, evaluate, and use. They must also recognize various factors influencing health literacy and use the factors as opportunities to optimize health literacy improvement. A health literacy approach can be applied by nurses to solve health problems and improve the quality of care for patients.